Oxidative balance score inversely associated with the prevalence and incidence of metabolic syndrome: analysis of two studies of the Korean population - Park, Hye-Min; Han, Tea-Hwa; Kwon, Yu-Jin; Lee, Jun-Hyuk (Frontiers in Nutrition, 2023)
Pro-oxidant/antioxidant imbalances leading to chronic inflammation and insulin resistance can contribute to the development of metabolic syndrome (MetS). Oxidative Balance Score (OBS), a comprehensive measure of exposure to pro-and anti-oxidants, represents an individual's total oxidative balance. This study aimed to evaluate the association between OBS and MetS using two large datasets. We analyzed data from 2,735 adults older than 19 years from the 2021 Korean National Health and Nutritional Examination Survey (KNHANES) and 5,807 adults aged 40-69 years from the Korean Genome and Epidemiology Study (KoGES). In each dataset, OBS was categorized into sex-specific tertiles (T). In KNHANES, the odds ratios and 95% confidence intervals for prevalent MetS in T3, compared to T1, were 0.44 (0.29-0.65) in men and 0.34 (0.23-0.50) in women after adjusting for confounders. In KoGES, the hazard ratios and 95% confidence intervals for incident MetS in T3, compared to T1, were 0.56 (0.48-0.65) in men and 0.63 (0.55-0.73) in women after adjusting for confounders. OBS appears to be inversely related to MetS, which suggests that adopting lifestyle behaviors that decrease oxidative stress could be an important preventive strategy for MetS.* p value for the comparison of the baseline characteristics among sex-specific tertile groups of oxidative balance score at the baseline survey.